Sistem Informasi Obat Di Apotek Nisa Berbasis Web - Dharmawan, Isov Dwi; , Nurgiyatna, ST., MSc., PhD (2016)
Nisa Pharmacy is a pharmacy that make the process of calculating the sales cure still use manual way, namely by noting the drug that has been sold and at what price to the general ledger. This manual method takes a lot of time and effort and most likely an error occurred. This study is intended to make the drug supply system that can simplify the calculations in the data processing. The purpose of this research is to design and create a web-based pplication that is useful in data processing drugs and complete information about the medicinal uses of existing drugs in pharmacies Nisa. The method used in this study is SDLC (System Development Life Cycle). Making this system using HTML programming language, bootstrap, and MySQL database. Results of the system that has been created is in the form of Nisa Pharmacy information system that can manage the drug information. The average values obtained from 3 respondents about the system is 85%. Pharmacists and the employees already tried the information system and the result is a system work, so that their work becomes more effective and efficient. This proves that these information systems are in accordance with user expectations.